Scrub typhus in pregnancy-a case series with variable presentation from mild to severe disease - Sheokand, Seema; Singh, Anju; Saha, Pradip K.; Meena, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Scrub typhus is an uncommon cause of acute febrile illness during pregnancy. It can lead to adverse maternal and fetal outcomes if not diagnosed early and treated appropriately. It manifests as mild febrile disease to severe form with multiorgan dysfunction. It might be clinically difficult to diagnose scrub typhus, hence it is important that those presenting with an acute febrile illness in endemic regions should have targeted investigations for early detection. Here we present successful management of three cases of scrub typhus in pregnancy with variable presentation of scrub typhus. Two of these presented in antenatal period whereas one in postnatal period resembling abdominal tuberculosis all three were tested COVID-19 (real time polymerase chain reaction) negative.